REKAYASA STRATEGI INVENTORY OPTIMAL PADA INDUSTRI JASA PARIWISATA - Sintyadi Thong (Operations Excellence: Journal of Applied Industrial Engineering, 2017)
One of the largest tour and travel service provider in Indonesia based in Jakarta has a traditional approach in maintaining its inventory which consists of mostly gimmicks and travel amenities. It mainly purchases goods for a whole year’s worth in order to achieve economies of scale and quantity discount without paying in regards to its actual demand conditions, as a result dead-stock is massive in number, and inventory costs are high. As an addition, this goes against green tourism philosophy. The purpose of this research is to maintain the inventory of the company by utilizing ABC Inventory model (y, R) EOQ model. With limited time as the main constraint to actually see the result of the proposed model, a computational simulation using Rockwell Arena is used to verify and measure the solutions. The result shows that with ABC Inventory model combined with (y,R) EOQ model, the company can reduce its inventory level especially on the most sensitive goods. A positive result is found on the second scenario during the 1st, 3rd, and 5th period where there is no instance of stockout.